2017
DOI: 10.1021/jacs.7b02581
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Facile Borane-Promoted, Rhodium-Catalyzed Asymmetric Hydrogenation of Tri- and Tetrasubstituted Alkenes

Abstract: Oxime-directed catalytic asymmetric hydroboration is diverted to catalytic asymmetric hydrogenation (CAH) upon the addition of a proton source, such as MeOH, or by running the reaction under a hydrogen atmosphere. A borane (e.g., pinacolborane) is required to promote CAH. Tri- and tetrasubstituted alkenes, including the challenging all-alkyl tetrasubstituted alkenes, undergo CAH with enantiomer ratios (er) as high as 99:1. The mild reaction conditions, i.e., ambient temperature, moderate reaction times, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The use of 0.5 equiv of HBpin could perfectly promote the hydrogenation reaction (eq 4). These results indicated that the HBpin or boronic group might promote the trisubstituted alkenylboronate hydrogenation process . These control reactions suggested that the reaction should undergo alkyne hydroboration followed by the HBpin-promoted alkene hydrogenation pathway.…”
mentioning
confidence: 99%
“…The use of 0.5 equiv of HBpin could perfectly promote the hydrogenation reaction (eq 4). These results indicated that the HBpin or boronic group might promote the trisubstituted alkenylboronate hydrogenation process . These control reactions suggested that the reaction should undergo alkyne hydroboration followed by the HBpin-promoted alkene hydrogenation pathway.…”
mentioning
confidence: 99%
“…In contrast, the 3‐ and 2‐thienyl derivatives are efficient substrates in the T2 b ‐catalyzed reaction, affording 5 o (85 %, 98:2 er) and 5 p (71 %, 96:4 er), respectively. The benzofuran derivative 3 q provides good regio‐ and enantioselectivity for 5 q (40 %, 94:6 er); the moderate yield reflects competing reduction in this case . The yields, regioselectivity, and enantioselectivity obtained for 5 k (60 %, 94:6) and 5 l (65 %, 95:5) are similar to those observed for the corresponding γ‐borated products.…”
Section: Figurementioning
confidence: 99%
“…An intriguing mode of olefin activation was recently disclosed by Takacs and co-workers at the University of Nebraska− Lincoln. 56 The group reported a remarkably facile boranepromoted, oxime-directed, and Rh-catalyzed AHTOs in high yields and with high selectivities (Figure 23). The mild protocol required short reaction times and only a slight excess above stoichiometric H 2 .…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%